Managing the load schedule of the administrative building taking into account emerging risks when connecting the kinetic energy storage to the power supply system - Shevchenko, S.Yu.; Savchenko, N.A.; Tretjak, A.V. (Електротехніка і електромеханіка, 2017)
Purpose. The purpose of the paper is to analyze load schedules of the administrative building and develop a structural scheme for connecting the kinetic energy storage in the power supply system of this building, which will allow using it as a consumer regulator, as well as a theoretical study of the risks that arise. Methodology. To conduct the research, the theory of designing internal electrical networks of buildings, the theory of plotting electric load graphs, methods of the theory of electromechanical systems and for analyzing the risk system, the T. Saati method of hierarchies were used. Results. The structure of kinetic energy storage (KES) connection to the power supply system of the administrative building is developed and the structural diagram of the KES proposed for installation is given, the average daily winter and summer load schedules are presented, a set of groups and subgroups of risks and their influence on the work of the power supply system of the building are connected with the connection of the KES. Originality. For the first time, the application of the kinetic energy storage in the power supply system of the building with the analysis of emerging risks is considered, which makes it possible to improve the reliability of the developed system and the efficiency of load regulation. Practical value. The application of the proposed scheme will make it possible to use administrative buildings as load regulators of the external power supply system, and also effectively manage the load in the internal power supply system of the building. Цель. Целью статьи является разработка структурной схемы подключения кинетического энергонакопителя в систему электроснабжения административного здания, что позволит использовать это здание в качестве потребителя - регулятора, а также теоретическое исследование возникающих при этом рисков. Методика. Для проведения исследований использовались теория проектирования внутренних электрических сетей зданий, теория построения графиков электрической нагрузки, методы теории электромеханических систем и для анализа системы рисков метод иерархий Т. Саати. Результаты. Разработана структура подключения кинетического энергонакопителя (КЭН) в систему электроснабжения административного здания и приведены суточные графики нагрузок, исследован набор групп и подгрупп рисков и их влияние на работу системы электроснабжения здания при подключении КЭН. Научная новизна. Впервые рассмотрено применение кинетического энергонакопителя в системе электроснабжения здания с анализом возникающих рисков, что позволяет повысить надежность работы разработанной системы и эффективность регулирования нагрузки. Практическое значение. Применение предложенной схемы позволит использовать административные здания в качестве регуляторов нагрузки внешней системы электроснабжения, а также эффективно управлять нагрузкой во внутренней системе электроснабжения здания.